Let the Ghosts Speak: An Empirical Exploration of the "Nature" of the Record - Lemieux, Victoria (Archivaria, 2001)
This article uses empirical data from a case study of record-keeping practices in indigenous Jamaican commercial banks that collapsed to explore the “nature” of the record. The article continues a thread of debate appearing in previous issues of Archivaria which questioned the definition of a record, whether the meaning of a record is fixed at the point of creation or evolves over time, and who authors the record. Drawing upon empirical data, the article finds support for the ideas of Preben Mortensen, Brien Brothman, and Tom Nesmith. Data are presented to illustrate the point that there is no single valid conceptualization of the record, but there are many valid conceptualizations arising from particular social contexts, and, further, that meaning in records is engendered over time by all those involved in the processes of incription, transmission, and contextualization, including record-keepers. Résumé Cet article se base sur des données empiriques, tirées d’une étude de cas portant sur les pratiques de gestion des documents dans les banques commerciales jamaïcaines qui ont fait banqueroute, afin d’explorer la «nature» des documents. Ils’inscrit dans le débat qui a eu lieu dans les pages des précédents numéros de la revue Archivaria portant sur la définition du document avec des questions sur le sens dudocument (est-il fixé au moment de la création ou évolue-t-il dans le temps?) et le créa-teur de celui-ci. Se basant sur des données empiriques, cet article prend appui sur les idées de Preben Mortensen, Brien Brothman et Tom Nesmith. Les données présentées dans l’article illustrent l’argument qu’il n’y a pas une seule façon de conceptualiser les documents mais plusieurs façons valables découlant des différents contextes sociaux etque, de plus, le sens des documents est produit, au cours du temps, par tous ceux quisont impliqués dans le processus de leur création, de leur transmission et de leur miseen contexte, dont les gestionnaires des documents.